Accelerating the development of biomarkers for drug safety : workshop summary - Olson, Steve, 1956-; Robinson, Sally; Giffin, Robert B. (National Academies Press, 2009)
"Biomarkers can be defined as indicators of any biologic state, and they are central to the future of medicine. As the cost of developing drugs has risen in recent years, reducing the number of new drugs approved for use, biomarker development may be a way to cut costs, enhance safety, and provide a more focused and rational pathway to drug development. On October 24, 2008, the IOM's Forum on Drug Discovery, Development, and Translation held "Assessing and Accelerating Development of Biomarkers for Drug Safety," a one-day workshop, summarized in this volume, on the value of biomarkers in helping to determine drug safety during development."